The Effects of Motivation on English Language Learning: A Case Study of Gems Public High School, Hujra Shah Muqeem. - Kanwal, Shaheen; Hashmi, Muhmmad Ahmad (JELLL, 2024)
In present time, English has reached at the level of global language and everyone has to learn it to fit into the real world and for communication purposes. Motivation is accepted as a fundamental factor for learning a language (EFL). This study overviews the research on the role of motivation in learning the language. In this paper, the researcher explains different types of motivation and reviews several studies related to the role of motivation. The data for this research study were collected online through google form and then analyzed. The findings illustrate that the students have improved themselves in this subject (English) after motivation. 200 responses were collected from Gems Public High school. The study examined many different factors that are having influence on students ‘motivation like their family back ground and parental ability etc. Different students learn English through different ways and to make student interested in learning a teacher should motivate his student because motivation plays a key role in learning a language particularly EFL.